Zinc-layered hydroxide with nitrate and phosphate as counter anions and its effect on growth performance of Kelampayan seedlings [Neolamarckia cadamba (Roxb.) Bosser] - Khadiran, Nor Farhana (2021)
Currently, layered hydroxide is subjected to intense research as this type of 2- dimensional (2D) nanomaterial can be used in various aspects of agriculture, particularly as a slow-release matrix of nutrients for plant growth. In this work, zinc layered hydroxide was synthesized by co-precipitation and anion exchange method which produces zinc layered hydroxide nitrate (ZLHN) and zinc layered hydroxide phosphate (ZLHP) nanofertilizer, respectively to evaluate the effect of nitrate and phosphate sorption efficiency towards plant growth. ZLHN and ZLHP showed the formation of a new peak of the basal interlayer spacing of 9.57 Å and 6.78 Å in the powder X-ray diffraction (PXRD) pattern, respectively. The FTIR, thermal, elemental, surface area and morphology analysis supported the formation of ZLHN and ZLHP nanofertilizer. The synthesized ZLH fertilizer was also tested for release kinetic studies while the bioassay was performed on Kelampayan (Neolamarckia cadamba) seedlings. The controlled release studies of ZLHN and ZLHP were carried out in deionized water, 0.005M sodium carbonate and soil media solution at pH 6.5. The highest percentage release was recorded to be 63.87% of nitrate in 0.005M sodium carbonate solution and 6.4% of phosphate in deionized water while the lower percentage release was recorded at 29.61% of nitrate and 0.21% of phosphate in soil media solution at 96 hours, respectively. The release profile was best fitted to the pseudo-second-order model with R2 values of 0.99 and 0.97 for ZLHN and ZLHP nanohybrid, respectively. The ZLH nanofertilizer were found to be non-toxic to plant, where all the green bean seeds were successfully germinated in the experiment. The percentage of seed germination can be arranged in order of ZLH nanofertilizer > commercial fertilizer > primary material treatment. Besides, after sixteen weeks of treatment of ZLH nanofertilizer toward the growth of kelampayan seedlings showed good performance and significant difference in diameter and height compared to other treatments. At the end of the study, the nutrient plant uptake was also determined and showed higher uptake in the leaves of Kelampayan treated with ZLH nanofertilizer and they are significantly higher compared to the other treatments. In conclusion, this study suggests that the development of ZLH nanofertilizer has the potential to be used as fertilizer nanodelivery systems.